Spirit possession and trance : new interdisciplinary perspectives - Schmidt, Bettina E.; Huskinson, Lucy, 1976- (Continuum advances in religious studies., 2010)
Spirit possession is a phenomenon that often elicits a response of fear, particular in those who are ignorant of its meaning and role within its particular religious and cultural traditions. Possession by divine beings (such as spirits or gods) is, however, €a key practice in religions worldwide. It is therefore important to gain an understanding of this practice in its cultural context before trying to develop a wider theory about it. This fascinating book contains several case studies that present new interpretations of spirit possession worldwide. The authors show the diversity of possi.